Pembelajaran Kitab Kuning dengan Bahasa Inggris di Pondok Pesantren Annuqayah Latee Guluk-Guluk Sumenep - Thorik Aziz; Akh Rosyidi (TADRIS: Jurnal Pendidikan Islam, 2020)
It was very rare the researchers who studied the learning of classical book with English in Islamic boarding schools, whereas learning classical book with English was really important for the progress of the times, santri who were studying classical book with English could simultaneously get two fields of science and could be a special attraction in preaching to face modern society. The results showed that, 1. The implementation of the learning classical book with English was carried out twice a week that was called as the first session and the second session, while the method used was Bandongan and discussion method. Bandongan was held in the first session and the discussion method was carried out in the second session. 2. The level of santri's understanding of learning classical book with English was very good. 3. The problems were the implementation of the first session was very early morning, santri’s understandings were different and some boards didn’t join the first session of program. Learning classical book using English was worth maintaining and continues to be developed. The positive influence was felt a lot by santri, besides being able to learn English that they could also learn classical book both nahwu-sharraf science and its contents.